Effect of social capital on adoption of climate-smart agriculture in Nyando Basin, Kenya - Birir, Alex (2020)
This Info Note summarizes findings of the project, “Using Climate-Smart Financial Diaries for Up-scaling in Nyando, Western Kenya”, led by the Amsterdam Center for World Food Studies (ACWFS) with participation of the CGIAR Research Program on Climate Change, Agriculture and Food Security (CCAFS) East Africa, the University of Nairobi’s School of Economics and Wageningen Economic Research. The findings are based on an analysis of baseline data collected from 122 households in 44 villages of Kericho and Kisumu Counties. The project focused on the extent of adoption of a number of CSA practices and their long-term impact on household income. The project also looked at the influence of social groups and social capital in the adoption of CSA, including membership in CBOs and social groups. Nyando is of interest due to the adverse effects of climate change and variability, and the various CSA technologies in practice which are aimed at making the local communities resilient to climate change. Of particular interest are CCAFS’ CSA technologies of improved breeds, agro-forestry, greenhouse farming and water harvesting.